Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

Let f : (–1, 1) ? R be a differentiable function with f(0) = – 1 and f '(0) = 1. Let g(x) = [f(2f(x) + 2)] 2,. Then g ' (0) =

Let f : (–1, 1) ? R be a differentiable function with f(0) = – 1 and f '(0) = 1. Let g(x) = [f(2f(x) + 2)] 2,.
Then g ' (0) =

Grade:12

1 Answers

SHAIK AASIF AHAMED
askIITians Faculty 74 Points
6 years ago
Hello student,
given f(0)=-1,f1(0)=1 and g(x)=2(f(2f(x)+2))2
g1(x)=2(f(2f(x)+2))[(f(2f(x)+2))][2f1(x)]
put x=0
g1(0)=2(f(2f(0)+2))[(f(2f(0)+2))][2f1(0)]=-4
Thanks and regards
Shaik Aasif
askIITians faculty

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free